Systemic Approach to Assessing Sustainable Development of the Regions - POPELO, Olha; TULCHYNSKA, Svitlana; KHARCHENKO, Yuliia; DERGALIUK, Bogdan; KHANIN, Semen; TKACHENKO, Tetiana (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021DO - 10.14505//jemt.12.3(51).13, 2021)
In modern conditions of the society development, there is a single direction of the development of national economies and their regions - through sustainable development. It is the consideration of the simultaneous economic, social and environmental direction of regional development that gives the greatest resultant effects of the territorial development. In turn, sustainable development requires the development of the  specific evaluation methods that can give sound, accurate results of assessing the state and dynamics of sustainable development of regions. The authors propose a methodological approach that involves determining the state and dynamics of sustainable development by determining the integrated index and its components by calculating the integrated sub-indices. The method of assessing the state and dynamics of sustainable development involves the use of disparate methods, including statistical, grouping, rationing, simulation, graphical and cartographic. In addition, the use of such mathematical techniques as: correlation analysis, multiple regression, cluster and factor analysis. The approbation of this method on the example of the regions of Ukraine is carried out. In turn, the obtained calculations of the sub-indices of economic, social and environmental components and sustainable development of the regions as a whole will contribute to the development of measures to increase the level of sustainable development and achieve its goals.